2022
DOI: 10.3390/nu14224718
|View full text |Cite
|
Sign up to set email alerts
|

The Lignan-Rich Fraction from Sambucus williamsii Hance Exerts Bone Protective Effects via Altering Circulating Serotonin and Gut Microbiota in Rats

Abstract: Our previous study revealed that the bone anabolic effects of the lignan-rich fraction (SWCA) from Sambucus williamsii Hance was involved in modulating the metabolism of tryptophan in vivo and inhibiting serotonin (5-HT) synthesis in vitro. This study aimed to determine how SWCA modulates bone metabolism via serotonin in vivo. The effects of SWCA were evaluated by using 4-month-old Sprague-Dawley (SD) ovariectomized rats. The serum levels of 5-HT and kynurenine, the protein expressions of tryptophan hydroxylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…A previous study has documented that serum 5-HT level is inversely associated with BMD in rats. 30 In women, decreased BMD is correlated with serotonergic antidepressant use. 31 Patients suffering from neuroendocrine tumors have decreased hip BMD and increased urinary 5-HIAA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has documented that serum 5-HT level is inversely associated with BMD in rats. 30 In women, decreased BMD is correlated with serotonergic antidepressant use. 31 Patients suffering from neuroendocrine tumors have decreased hip BMD and increased urinary 5-HIAA.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of serotonin, kynurenine (Kyn), their respective isotopologs (D 4 -serotonin, D4-L-Kyn), and internal standard (IS, 5-Methoxytryptamine) was performed on an ACQUITYTM UPLC system (Waters Corp., Milford, CT, USA) coupled to a Xevo TQ-XS mass spectrometer (Waters Corp.), as described in our previous study [7] .…”
Section: Determination Of Serum Serotonin Level Using Ultra Performan...mentioning
confidence: 99%
“…Cell culture and MTS assay RBL2H3 cells were purchased from Procell (Wuhan, China) and cultured routinely in the medium and under the conditions described in our previous study [7] . Cells were seeded at a density of 1 × 10 4 and 5 × 10 4 cells per well in 96-well plates and 24-well plates, respectively.…”
Section: Surface Plasmon Resonance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…5.1.39BFAA was negatively correlated with the level of enterolactone. In a study on rats, Xiao et al [ 84 ] showed that lignans mainly escalated the abundance of Antinobacteria and modulated several genera relating to bone mineral density, achieving the effect of alleviated bone loss and decreased serum levels of serotonin.…”
Section: The Effect and Application Potential Of Plant-derived Bioact...mentioning
confidence: 99%